2013
DOI: 10.1097/psy.0b013e31827612a6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Procedures, Revascularization, and Inpatient Mortality After Acute Myocardial Infarction in Patients With Schizophrenia and Bipolar Disorder

Abstract: In a large national sample and in the context of a comprehensive free health service, patients with schizophrenia and bipolar disorder were substantially disadvantaged, being half as likely to receive catheterization or revascularization procedures after AMI. Further research is required to clarify the reasons for this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 37 publications
(40 reference statements)
7
48
0
1
Order By: Relevance
“…According to our hypothesis, the lower rate of PSA tests could suggest that this negative association may reflect more an issue of method than an issue of substance. Since service-based disparities were noted repeatedly in the literature [9][10][11] , as well as in our data (Gal et al, submitted), it is possible that the lower rate of PSA tests among service users diagnosed with schizophrenia result in less biopsies, and the consequent lower rate of cancer diagnosis. This interpretation should be carefully weighted given the relatively lower rate of performance of PSA test preceding the cancer diagnosis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…According to our hypothesis, the lower rate of PSA tests could suggest that this negative association may reflect more an issue of method than an issue of substance. Since service-based disparities were noted repeatedly in the literature [9][10][11] , as well as in our data (Gal et al, submitted), it is possible that the lower rate of PSA tests among service users diagnosed with schizophrenia result in less biopsies, and the consequent lower rate of cancer diagnosis. This interpretation should be carefully weighted given the relatively lower rate of performance of PSA test preceding the cancer diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…Limited heterosexual activity with a subsequent decreased risk of sexual-transmitted infections. However, a methodological hypothesis cannot be excluded: given the disparities in the health care of persons with schizophrenia [9][10][11] , if service-users with schizophrenia are less often screened with prostate-specific antigen (PSA) tests compared to schizophrenia-free men the identification of prostate cancer may fall. We had the rare opportunity to explore the latter hypothesis in a study of medical services provided to persons with schizophrenia in a country with a national health insurance.…”
Section: Introductionmentioning
confidence: 99%
“…; Wu et al . ), while four studies found no significant difference in mortality after adjusting for demographic and medical factors (Bot et al . ; Buller et al .…”
Section: Resultsmentioning
confidence: 99%
“…; Wu et al . ). The use of hospital databases provided for standardized definitions across studies (ICD‐9‐CM coding) reduces bias in sample selection across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…For more than a generation, the field of psychosomatic medicine has described the strong adverse impact of psychiatric illnesses on the course and outcome of a wide range of comorbid medical diseases, including cancer, cardiovascular disease, diabetes, and HIV/AIDS (1)(2)(3)(4). These relationships stubbornly persist in the absence of effective evidence-based strategies for disrupting the interplay between psychiatric and nonpsychiatric illness.…”
mentioning
confidence: 96%